Review of hydro-economic models to address river basin management problems: structure, applications and research gaps - Bekchanov, Maksud; Sood, Aditya; Jeuland, M. (International Water Management Institute, 2015)
Across the globe, the prospect of increasing water demands coupled with the potential for reduced water availability is calling for implementation of a range of technological, institutional, and economic instruments to address growing water scarcity. Hydro-economic models (HEMs), which integrate the complex hydrologic and economic interrelationships inherent in most water resources systems, provide an effective means of diagnosing and devising solutions to water-related problems across varied spatial and temporal scales. This study reviews recent advances in hydro-economic modeling and characterizes the types of issues that are typically explored in the hydro-economic modeling literature. Our findings suggest that additional efforts are needed to more realistically account for the range and complexity of interlinkages between water systems and society, particularly with regards to ecology and water quality, and the food and energy sectors. Additionally, the forces that depend on water and operate on the broader economy, for example in interregional trade should be investigated further. Moreover, effects on the distribution of income within countries, and on migration should be considered in basin management modeling studies.